Removal of penicillin G and sulfadiazine by GAC adsorption - Tan, Wei Liang (2018)
Contamination caused by antibiotics has been increasing as most of them are highly persistent in the environment. Antibiotics are commonly released into the water bodies through direct discharge from wastewater treatment plants and pharmaceutical plants. Impacts caused by these antibiotics to both the ecosystem and human health has become a serious problem. Hence, there is an urgent need to explore the ways of how to remove these antibiotics before discharging into the environment. As antibiotics are anti-bacterial in nature, biological removal of these chemicals has been demonstrated to be ineffective, while the use of technologies, such as advanced oxidation appears to be uneconomic and hard for treating a large amount of wastewater at an affordable cost. Thus, for antibiotics adsorption at various concentrations, granular activated carbon (GAC) was selected, in order to determine adsorption effectiveness for removing antibiotics from aqueous solution. For this purpose, two model antibiotics, Penicillin G (PCG) and Sulfadiazine (SDZ) were selected. Batch adsorptions experiments were carried out by mixing the antibiotics solution with GAC. The GAC adsorption results were analysed through the studying of adsorption isotherms followed by the study of adsorption kinetics. As for the study of adsorption isotherms, the isotherms selected were Langmuir and Freundlich while pseudo-first and pseudo-second order were selected for the kinetics study. The results concluded that Langmuir isotherm gave a more suitable description of the adsorption process as compared to Freundlich isotherm for both types of antibiotics, with R2 value of 0.9456 for PCG and 0.9192 for SDZ. As for adsorption kinetics of PCG and SDZ, both pseudo-first and pseudo-second orders indicated that they were appropriate as the values of their R2 were more than 0.89, but with pseudo-second order showing a better fitting of the graphs. The maximum adsorption amount of SDZ by GAC was 243.902 mg/g while for PCG was 192.308 mg/g. This proved that adsorption of SDZ by GAC was more effective.